2016
DOI: 10.1016/j.adolescence.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inter‐parental conflict on adolescent delinquency via school connectedness: Is impulsivity a vulnerability or plasticity factor?

Abstract: This study examined the mediating effect of school connectedness on the relationship between inter‐parental conflict and adolescent delinquency, and impulsivity's moderation of the conditional effect of school connectedness. In total, 1407 Chinese students (mean age = 12.74 years, SD = 0.57) from 4 middle schools completed anonymous questionnaires regarding inter‐parental conflict, impulsivity, school connectedness, and delinquency. Path analysis revealed school connectedness was a mediator in the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…For each participant, his/her average score for all 17 items was determined, with higher scores indicating higher levels of interparental conflict. The scale has shown good reliability in previous research (Chi and Xin, 2003;Liu et al, 2016). For the current study, the measure demonstrated outstanding reliability (α = 0.90).…”
Section: Interparental Conflictsupporting
confidence: 59%
See 2 more Smart Citations
“…For each participant, his/her average score for all 17 items was determined, with higher scores indicating higher levels of interparental conflict. The scale has shown good reliability in previous research (Chi and Xin, 2003;Liu et al, 2016). For the current study, the measure demonstrated outstanding reliability (α = 0.90).…”
Section: Interparental Conflictsupporting
confidence: 59%
“…Given the relatively high correlations among these five dimensions (i.e., negative urgency, premeditation, perseverance, sensation seeking, and positive urgency), a composite score was created for each participant by determining his/her overall average score for all 20 items; higher scores indicated higher levels of impulsivity. Many empirical studies have used the UPPS-P Scale to measure adolescent impulsivity and have calculated the mean scores for all items when performing their analysis (Liu et al, 2016;Zhu et al, 2016). For this study, the UPPS-P Scale demonstrated excellent reliability (Cronbach's alpha = 0.82).…”
Section: Covariatesmentioning
confidence: 83%
See 1 more Smart Citation
“…According to the stress-buffering model (Cohen and Wills, 1985), adolescents with strong school connectedness are more likely to accept the school’s norms, values, and expectations, and to refrain from aggressive behavior, given that problematic behaviors are inconsistent with the regulations of the school (Loukas and Pasch, 2013; Liu et al, 2016). Moreover, adolescents with high school connectedness may recognize the negative effects of psychological control and deviant peer affiliation, and they may be buffered by desire to obey the rules or fear of getting caught (Loukas and Pasch, 2013; Liu et al, 2016; Loke et al, 2016). Finally, school connectedness may be protective for adolescents under psychological control, by motivating them to conform to social regulations and by decreasing the likelihood of their engaging in deviant activities (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adolescents with high school connectedness may recognize the negative effects of psychological control and deviant peer affiliation, and they may be buffered by desire to obey the rules or fear of getting caught (Loukas and Pasch, 2013; Liu et al, 2016; Loke et al, 2016). Finally, school connectedness may be protective for adolescents under psychological control, by motivating them to conform to social regulations and by decreasing the likelihood of their engaging in deviant activities (Liu et al, 2016). Based on these theoretical suggestions and indirect experimental evidence, we expect that school connectedness would weaken the mediating effect of deviant peer affiliation toward the influence of psychological control on adolescent aggression.…”
Section: Introductionmentioning
confidence: 99%